The influence of pH on solubility of copper in soils contaminated by copper industry in Legnica = Wpływ pH na mobilność miedzi w glebach zanieczyszczonych przez przemysł miedziowy w Legnicy - Cuske, Mateusz; Gersztyn, Leszek; Karczewska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the study was to determine the influence of changes in pH on the solubility of copper in soils contaminated by copper industry. Soil samples were collected from the surface soil horizon (0-30 cm) at two sites situated in the vicinity of Legnica Copper Smelter. Soil material contained various concentrations of total Cu.
Keywords: gleba; miedź; mobilność miedzi; zanieczyszczenie gleby; Huta Miedzi Legnica; soil; cooper; copper mobility; soil pollution; Legnica Copper Smelter